Dual electro-optical modulator polarimeter based on adaptive optics scanning laser ophthalmoscope - Song, Hongxin (Optical Society of America, 2010)
We constructed a high speed and high-resolution Stokes vector retinal imaging polarimeter with dual electro-optical modulators based on adaptive optics scanning laser ophthalmoscope. By varying the voltages on the EO crystals line by line, we were able to measure over 500,000 Stokes vectors per second. We used this system in three human subjects demonstrating the capability of the system to be employed in vivo. The high speed effectively decreases the adverse impact of eye motion induced errors in polarization calculations, improving the contrast of retinal structures based on their polarization properties.